Assessing Surface Water Contamination by Toxic Metals Via Bioindicators: Public Health Implications (International Journal of Environmental Sciences, 2025)
This study presents the results of heavy metal concentrations in aquatic mosses collected from the Ave River Basin during two field surveys (campaigns II and III) and a comparison with data from a field survey carried out 15 years earlier (campaign I). The findings indicated high levels of chromium in the samples from the two previous campaigns, along with aggravated contamination of cadmium, lead, and zinc compared to campaign I. The order of metal accumulation in the moss samples, from highest to lowest, was Fe > Zn > Cu > Cr > Ni > Pb > Cd > Hg. The Metal Pollution Index (MPI) revealed changes in contamination levels between campaigns. Most stations experienced a decrease in classification due to increased water flow and reduced accumulation during Campaign II. The contamination patterns suggest the influence of industrial activities, particularly metal coating facilities. Monitoring and mitigation efforts are necessary to address persistent heavy metal pollution in the Ave River Basin.